EVALUASI PELAYANAN PUBLIK DI KECAMATAN KEMUNING KOTA PALEMBANG PASCA PEMEKARAN TAHUN 2008-2013 - Putra Astaman; Rendy Sueztra Canaldhy; Ryllian Chandra (Jurnal Pemerintahan dan Politik, 2019)
The research focus is on the evaluation of public services in the district kemuning Palembang. There are some problems that the background for researchers in conducting this study include the absence of changes or improvements in public services performed after the division of the districts, education facilities and health is minimal, quality and performance of personnel resources that have not been reflected as personnel resources that have integrity in doing his job. The purpose of this study was to answer the problem formulation on how the evaluation of public services in the district after the division of the city of Palembang. The method used in this research is descriptive qualitative data collection techniques is done through a literature review and interviews with select informants deemed technically competent da knowing the problems that occur in the field, the data obtained is then analyzed qualitatively. From the results of the study illustrate that public service delivery is done after splitting dilakukannnya districts has not undergone significant changes. It is seen from the analysis of the results of interviews and observations indicate that indeed there has been no change so significantly to pubic services in the district kemuning Palembang.Keywords : Evaluation, Public Service, Kemuning.